CORRELATIONS BETWEEN THE AGE OF FIRST MARRIED, CONTRACEPTION USE AND FAMILY HISTORY WITH CERVICAL PRECANCER IN WOMEN OF CHILDBEARING AGE AT METRO CITY HEALTH CENTER - Yuliawati Yuliawati; Martini Martini; Septi Widiyanti (Institute of Computer Science (IOCS), 2022)
Cervical cancer is one of the main causes of death in women not only in Indonesia but also in the world. Cervical cancer can cause damage to other organs and can cause death. The purpose of the study was to determine the relationship between age at first marriage, use of contraceptives, family history and the incidence of cervical precancer in women of childbearing age at the Metro City Health Center. This research is a case control. The sample size is 72 respondents divided into 11 case groups: 61 control groups. Sample selection using Simple Random Sampling. Secondary data obtained from the medical records and primary data obtained by interview. The results from 72 respondents turned out to be: Proportion: age at first marriage Age 20 years: 38.9%, hormonal contraception: 63.9%, There is no relationship between the incidence of cervical pre-cancer with age at first marriage (P value = 1000), using hormonal contraception (P value = 0.048) and There is a significant relationship between pre-cervical cancer and a family history (OR = 0.116) means that respondents who have a family history have 0.116 times the chance of IVA (+) compared to respondents who have no family history of cervical cancer